Výzkum organizačního uspořádání logistiky v podnicích chemického průmyslu - Vlčková, Vladimíra (Univerzita Pardubice, 1999)
In the first part of this paper the theoretical aspects of logistic subdivision integration into corporate structure of any enterprise are given. Further results of research work done in enterprises of chemical industry by the help of written and/or personal inquiring are summarised. The main aim of this research has been to find out and describe present development and status quo in logistic systems introduction into Czech chemical enterprises. The analysis of logistic organisational ordering and identification of 25 different logistic activities, which are included in competence of logistic subdivision, are done as well.
Keywords: podniky; chemický průmysl; Logistika; organizace; Výzkum